FERMENTATIVE-MODIFICATION OF SORGHUM AND MILLET BIOPOLYMERS: IMPACT ON FUNCTIONAL PROPERTIES, PROXIMATE COMPOSITION, AMINO ACIDS AND PROTEIN QUALITY OF MODIFIED FLOURS - SULEIMAN YUSUF BAGIREI; IROH NKAMA; MAMUDU HALIDU BADAU; YAHAYA SAYYADI MOHAMMAD (Journal of Engineering Studies and Research)
Fermentation is being used in the preparation of cereal-based foods to impart changes that can influence the character of the final product, but the processes of are tedious, unhygienic and labor intensive. Scientific improvements can facilitate product standardization, specification, safety and availability. Fermentative modification of the sorghum and millet grains biopolymer was achieved by natural fermentation at 34 oC for 36hours, with the fermentation water being changed every 12 hours. The grains were decanted and dried in a solar dryer at 41 oC, ground and sieved through a 300 μm sieve, while laboratory analyses carried out by standard methods. The functional properties, proximate composition, amino acids profile and protein quality indices of the flours were determined using standard methods. The process led to reduction in functional properties and proximate composition but carbohydrate and energy values were not affected while protein contents were increased by 7.5 % for sorghum and 9.7 % for millet. Reduction of 11.5 % and 17.2 % in leucine and phenylalanine contents respectively were recorded in sorghum, but in millet the values increased by 15.8 % and 6.6 % respectively. There were 2.9 % and 20.6 % increase in lysine and tryptophan contents in sorghum and a decrease of 13.5 % and 7.7 % respectively in millet. There were increases in histidine, isoleucine, methionine, threonine, and valine.